Abram Slutskin and Radiophysics in Ukraine of the First Half of the 20th Century: World Dimension - Tverytnykova, Elena; Gutnyk, Maryna (Polish Academy of Arts and Sciences, 2022)
The article discusses the scientific and pedagogical activity of the outstanding Ukrainian radiophysicist Abram Slutskin in the context of the development of world radiophysical research. It is substantiated that the theoretical works of the scientist defined a new direction of research in Ukraine, namely the radar, and were important for the development of ultrahigh frequency physics. Innovative research initiated by Abram Slutskin found application in new defense technologies, military equipment, and special devices for medicine, biology, navigation, communications, household television and the radio industry. The article proves that Abram Slutskin had priority in launching research in the field of biophysics in Ukraine. The research on the use of ultrahigh frequencies for treatment of oncological patients carried out by scientists were unique for that time. Abram Slutskin᾽s graduate students became well-known specialists, who further developed the scientist’s ideas by initiating innovative areas of research and creating new institutions. We have grounds to consider Abram Slutskin as one of the founders of the Ukrainian scientific radio-physical school.

Tekst przedstawia działalność naukową i pedagogiczną wybitnego ukraińskiego radiofizyka Abrama Słutckina w kontekście rozwoju światowych badań radiofizycznych. Udowodniono, że prace teoretyczne naukowca wyznaczyły nowy kierunek badań na Ukrainie – technikę radarową i miały znaczenie dla rozwoju fizyki ultrawysokich częstotliwości. Innowacyjne badania zainicjowane przez Abrama Slutskina znalazły zastosowanie w tworzeniu nowych technologii obronnych, sprzętu wojskowego, urządzeń specjalnych dla medycyny, biologii, nawigacji, łączności, telewizji domowej i przemysłu radiowego. Udowodniono, że Abram Slutskin był prekursorem badań w dziedzinie biofizyki na Ukrainie. Wyjątkowe jak na tamte czasy były prowadzone przez naukowców badania nad wykorzystaniem ultrawysokich częstotliwości w leczeniu chorych na raka. Doktoranci Abrama Slutskina stali się znanymi specjalistami, którzy rozwinęli idee naukowca w zakresie wytyczania innowacyjnych obszarów badań i tworzenia nowych instytucji. Daje to podstawy do uznania Abrama Słuckina za jednego z założycieli ukraińskiej naukowej szkoły radiofizycznej.
Abram Slutskin i radiofizyka na Ukrainie w pierwszej połowie XX wieku: światowy wymiar
Keywords: radiophysics; magnetron; radar; Slutskin; Ukrainian scientists; radiofizyka; magnetron; radar; Abram Słuckin; ukraińscy naukowcy